2017
DOI: 10.1155/2017/1054129
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between Tissue Characterization and Dynamic Expression of Matrix Metalloproteinase-2 and Its Tissue Inhibitor in Conjunctival Filtering Bleb of Rats

Abstract: Purpose Using rat conjunctival bleb model, we correlated changes morphology and histology in the bleb with changes in MMP-2 and TIMP-2 levels. Methods Filtering surgeries were performed on rats. Dynamic changes in morphology and histopathology were observed using HE staining. Expression of MMP-2 and TIMP-2 was determined by immunofluorescence microscopy and western blotting. Results Well-elevated filtering blebs formed and persisted for an average of 12 days. Histological examination showed that inflammatory w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…Shima et al [ 10 ] detected expression of MMP-1 at the protein and mRNA levels by establishing a rabbit model of filtrating bleb scarring formation. Previous studies of conjunctival filtration bleb formation and scarring in rats suggested the dynamic expression of MMP-2 and TIMP-2 and the balance between these two proteins was closely related to the scarring of filtrating blebs [ 11 ]. Further studies on the specific inhibitory effect of TIMP-2 on MMP-2 may improve the success rate of filtration surgery by degrading the ECM of fibroblasts in Tenon's capsule and thus inhibiting filtration bleb scarring.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Shima et al [ 10 ] detected expression of MMP-1 at the protein and mRNA levels by establishing a rabbit model of filtrating bleb scarring formation. Previous studies of conjunctival filtration bleb formation and scarring in rats suggested the dynamic expression of MMP-2 and TIMP-2 and the balance between these two proteins was closely related to the scarring of filtrating blebs [ 11 ]. Further studies on the specific inhibitory effect of TIMP-2 on MMP-2 may improve the success rate of filtration surgery by degrading the ECM of fibroblasts in Tenon's capsule and thus inhibiting filtration bleb scarring.…”
Section: Discussionmentioning
confidence: 99%
“…Our previous study showed that scar formation during wound repair was most critical within two weeks after surgery [ 11 ]. From days 1–3, HE staining revealed that the connective tissue of the bulbar conjunctiva was markedly oedematous and loose, with vascular dilation and containing an abundance of infiltrating neutrophils.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, the induction of glaucoma animal models is highly recommended prior to glaucoma filtering surgeries (GFS) so as to more scientifically assess the effect and draw more convincing conclusions [3]. Currently, most studies used normal ocular tension animals to observe the postoperative scarring inhibition effect of new drugs and new equipment [4][5][6]. Different from the intraocular hypertension (OHT) model, the normal IOP animals may lead to potential biases in the research results.…”
Section: Introductionmentioning
confidence: 99%